Imaging Venous Thromboembolism with Emphasis on Ultrasound, Chest CT, Angiography and Echocardiography - Torbicki, Adam (Thrombosis and Haemostasis, 1999)
The clinical diagnosis of venous thromboembolism (VTE) is dif ficult and sometimes unreliable. Pulmonary angiography and contrast venography are used as reference tests for pulmonary embolism (PE) and deep vein thrombosis (DVT), respectively.1,2 However, due to the invasive nature of these reference tests, the optimal and clinically acceptable diagnosis of VTE remains a matter of some debate. Until recently, standard diagnostic strate gy in suspected pulmonary embolism (PE) consisted of a lung perfusion scan, followed by venous ultrasound (VUS), if a lung perfusion scan did not produce a definitive diagnosis. Eventually pulmonary angiography was performed.3,4 In clinical practice this strategy has rarely been respected because it required many pulmonary angiographic examinations. Diagnostic managemen was often halted prematurely without performing pulmonary angiography and, thus, without final confirmation or exclusion o PE.5-7 In addition, suspected DVT is often managed only on the basis of single VUS examination, which, unfortunately, has a rel atively low sensitivity when used to visualize the vasculature below the knee.8This chapter focuses on newer, noninvasive diagnostic tests that permit direct imaging of venous thromboemboli. While the place of those tests in diagnostic algorithms remains to be fully determined, they may already be helpful in simplifying the diagnostic management of patients in many clinical situations including those patients at high-risk of venous thromboem bolism. These patients represent a non-homogeneous group such as patients with recent major surgery, serious medical dis eases, or a concomitant history of VTE or thrombophilia According to a recent consensus statement, screening for VTE is technically possible, but, in the presence of effective prophy laxis, neither was demonstrated to be necessary or cost effec tive.9 Therefore, the main effort should be focused on effective diagnostic management of those patients who present with symptoms and/or signs suggestive of VTE.